An Analysis of Intersection of Culture Rights with Basic Human Rights Standards in the Context of Nepal (Tribhuvan University Law Journal, 2025)
Basic human rights are entitled to everyone as inherent and natural by virtue of being human. The nature of basic human rights is universal and enforcement of those rights has to be guaranteed by the state apart they belongs to certain groups and tribes in terms of various socio-economic status. Often it has been clearly visible that there are some challenges to enforcement of basic human rights due to different socio-cultural practices, believes and the way of life of the people. Moreover, some people are practicing such socio-cultural practices which are not only traditional often some of them are also harmful to human as well. Specially, in the situation of conflict between basic human rights and rights of socio-cultural practices, an issue raises is which rights supersedes the other. There is no unanimous principle or value is being established yet, however based upon prevailing international and national legal human rights frameworks and judicial decisions, the crux is to create enabling utmost enabling environment to flourish all basic human rights of everyone.